The isolation of Kemerovo group orbiviruses and Uukuniemi group viruses of the family bunyaviridae from Ixodes uriae ticks from the Isle of May, Scotland - Spence, R P; Harrap, K A; Nuttall, P A (Acta virologica (Anglickâa verze), 1985)
Viruses isolated from ticks (Ixodes uriae) from a seabird colony on the Isle of May, Scotland, were shown by complement fixation tests to be related to the Uukuniemi and Kemerovo serogroups. Electron microscopic studies on the Uukuniemi viruses showed them to have a morphology characteristic of the bunyaviridae, and the Kemerovo group to be characteristic of orbiviruses. Separate isolates from the two serogroups were distinguished from each other by neutralization tests.